WNK3 kinase maintains neuronal excitability by reducing inwardly rectifying K+ conductance in layer V pyramidal neurons of mouse medial prefrontal cortex - Sinha, Adya Saran; Wang, Tianying; Watanabe, Miho; Hosoi, Yasushi; Sohara, Eisei; Akita, Tenpei; Uchida, Shinichi; Fukuda, Atsuo (Frontiers in Molecular Neuroscience, 2022)
The with-no-lysine (WNK) family of serine-threonine kinases and its downstream kinases of STE20/SPS1-related proline/alanine-rich kinase (SPAK) and oxidative stress-responsive kinase-1 (OSR1) may regulate intracellular Cl− homeostasis through phosphorylation of cation-Cl− co-transporters. WNK3 is expressed in fetal and postnatal brains, and its expression level increases during development. Its roles in neurons, however, remain uncertain. Using WNK3 knockout (KO) mice, we investigated the role of WNK3 in the regulation of the intracellular Cl− concentration ([Cl−]i) and the excitability of layer V pyramidal neurons in the medial prefrontal cortex (mPFC). Gramicidin-perforated patch-clamp recordings in neurons from acute slice preparation at the postnatal day 21 indicated a significantly depolarized reversal potential for GABAA receptor-mediated currents by 6 mV, corresponding to the higher [Cl−]i level by ~4 mM in KO mice than in wild-type littermates. However, phosphorylation levels of SPAK and OSR1 and those of neuronal Na+-K+-2Cl− co-transporter NKCC1 and K+-Cl− co-transporter KCC2 did not significantly differ between KO and wild-type mice. Meanwhile, the resting membrane potential of neurons was more hyperpolarized by 7 mV, and the minimum stimulus current necessary for firing induction was increased in KO mice. These were due to an increased inwardly rectifying K+ (IRK) conductance, mediated by classical inwardly rectifying (Kir) channels, in KO neurons. The introduction of an active form of WNK3 into the recording neurons reversed these changes. The potential role of KCC2 function in the observed changes of KO neurons was investigated by applying a selective KCC2 activator, CLP290. This reversed the enhanced IRK conductance in KO neurons, indicating that both WNK3 and KCC2 are intimately linked in the regulation of resting K+ conductance. Evaluation of synaptic properties revealed that the frequency of miniature excitatory postsynaptic currents (mEPSCs) was reduced, whereas that of inhibitory currents (mIPSCs) was slightly increased in KO neurons. Together, the impact of these developmental changes on the membrane and synaptic properties was manifested as behavioral deficits in pre-pulse inhibition, a measure of sensorimotor gating involving multiple brain regions including the mPFC, in KO mice. Thus, the basal function of WNK3 would be the maintenance and/or development of both intrinsic and synaptic excitabilities.